Manual de funcionamiento, mantenimiento y aplicación pedagógica de la mezcladora de carne para el laboratorio de investigación en cárnicos de la carrera de Agroindustria de la Universidad Técnica de Cotopaxi. - Cumbajín Carrillo, Lisseth Alexandra (2022)
The elaboration of this integrative project covers several topics that allow a proper use of the meat mixer, this allows handling the equipment in a better way, and also refers to the four main maintenance that are routine, preventive, predictive and corrective, which are required to prevent the deterioration of the mixer, based on the knowledge of its characteristics and parts that compose it, before, during and after having acquired it. The present work contains the description of the meat mixer, identifying its main characteristics, which leads to the adequate use of the equipment, without causing risks in its use and handling. When analyzing the necessary equipment for the complementation of the theoretical learning with the experimental and practical part, in the integral formation of the Agroindustrial Engineer in the Technical University of Cotopaxi; detecting that the innovation of an equipment with the optimal characteristics was needed, it is thus that when implementing the meat mixer it is verified The benefits of the equipment in conjunction with other complementary machinery in the manufacture of meat products were verified. An experimental activity was carried out on the production of sausages, in this case, chicken sausage and Frankfurt, thus showing its good functionality, after which the respective calculations were made in terms of the balance of matter required in the process. Finally, it is mentioned that the product elaborated in the aforementioned practice is a quality product, required for the good nutrition of the consumer public.